Non-canonical NRF2 activation promotes a pro-diabetic shift in hepatic glucose metabolism - Pengfei Liu; Matthew Dodson; Hui Li; Cody J. Schmidlin; Aryatara Shakya; Yongyi Wei; Joe G.N. Garcia; Eli Chapman; Pawel R. Kiela; Qing-Yu Zhang; Eileen White; Xinxin Ding; et al. (Elsevier, 2021)
Objective: NRF2, a transcription factor that regulates cellular redox and metabolic homeostasis, plays a dual role in human disease. While it is well known that canonical intermittent NRF2 activation protects against diabetes-induced tissue damage, little is known regarding the effects of prolonged non-canonical NRF2 activation in diabetes. The goal of this study was to determine the role and mechanisms of prolonged NRF2 activation in arsenic diabetogenicity. Methods: To test this, we utilized an integrated transcriptomic and metabolomic approach to assess diabetogenic changes in the livers of wild type, Nrf2−/−, p62−/−, or Nrf2−/−; p62−/− mice exposed to arsenic in the drinking water for 20 weeks. Results: In contrast to canonical oxidative/electrophilic activation, prolonged non-canonical NRF2 activation via p62-mediated sequestration of KEAP1 increases carbohydrate flux through the polyol pathway, resulting in a pro-diabetic shift in glucose homeostasis. This p62- and NRF2-dependent increase in liver fructose metabolism and gluconeogenesis occurs through the upregulation of four novel NRF2 target genes, ketohexokinase (Khk), sorbitol dehydrogenase (Sord), triokinase/FMN cyclase (Tkfc), and hepatocyte nuclear factor 4 (Hnf4A). Conclusion: We demonstrate that NRF2 and p62 are essential for arsenic-mediated insulin resistance and glucose intolerance, revealing a pro-diabetic role for prolonged NRF2 activation in arsenic diabetogenesis.